A competency framework for fire safety engineering. (January 2022) - Lange, David; Torero, Jose L.; Spinardi, Graham; Law, Angus; Johnson, Peter; Brinson, Ashley; Maluk, Cristian; Hidalgo, Juan P.; Woodrow, Michael
Abstract: Fire safety engineering accreditation and licensing is a subject of much debate in many jurisdictions especially following the Grenfell Tower fire and as a result of the many issues that have been brought to light following similar cladding related fires around the world. It is argued elsewhere that the lack of a well defined accreditation and licensing framework is one of the most significant weaknesses in the provision of fire safety engineering services in some jurisdictions; and in other jurisdictions where these frameworks do exist, they lack a well articulated definition of competency that fully reflects the expectations of those seeking to enter the profession. This paper discusses the motivation for stronger accreditation of fire safety engineers. Describing an idealised accreditation system, the unique role of the fire safety engineer is then discussed as is the need to redefine competency expectations to reflect the current needs of the public who the profession serves. Finally, a proposed competency framework is detailed. This links technical competencies to the skill in their application to complex engineering problems – namely the design of a fire safety strategy, and also highlights additional non-technical competencies which should be expected of those seeking to enter the profession.